What are jellyfish really eating to support high ecophysiological condition? - Morais, Pedro (2016)
The feeding ecology of Blackfordia virginica was evaluated concurrently with their ecophysiological condition in a temperate estuary. The diet of B. virginica is composed not only of metazooplankton, as commonly observed for other jellyfish species, but also of phytoplankton, ciliates and detritus. This feeding behavior might explain their good nutritional condition and sustainable growth during bloom peaks, when zooplankton abundance has already decreased significantly.